Yambo: between dismemory and rememoration - Zaganin Rosa, Paulo Fernando [UNESP] (Univ Estadual Paulista-unesp, 2016)
Umberto Eco is the author of several theoretical texts that are fundamental for understanding contemporary art work. In 1980, he had his first experience as a novelist with the publication of The name of the rose, which was followed by six other novels. In this paper, we will focus on Eco's fifth novel, entitled The mysterious flame of queen Loana (2005), an edition that is full of illustrative material and a mixture of documents that refer to the years 1930-40, which present an overview of Italy at that time. The protagonist, a bibliophile who is called by his nickname, Yambo, loses personal memory, but keeps the bookish one intact. To try to retrieve it, he returns to his family's old house, located in Solara, in the mountains of Piedmont, where he ends up finding objects and information that relate to his youth - Fascism and World War II in Italy. Thus, our goal will be to verify how the presence of these elements results in a literary text that is able to discuss the relationship between individual memory and collective memory, as well as the constitution of individual and national Italian identities.
Keywords: Umberto Eco; The mysterious flame of queen Loana; Italian literature; Poetics of memory